The Role of Gut Microbiome Alterations in the Pathogenesis and Management of Sjögren’s Syndrome - Koralewicz, Mateusz; Szatkowska, Olga; Choinka, Martyna; Tschuschke, Max; Wdowiak, Natalia; Adamska, Kinga (Quality in Sport, 2024)
Sjögren’s syndrome (SS) is a systemic autoimmune disorder characterized by inflammation and damage to the exocrine glands, leading to symptoms such as ocular and oral dryness, and a range of extraglandular manifestations including polyneuropathies, lung and kidney dysfunction, and systemic vasculitis. Although the exact etiology of SS remains unclear, recent research has highlighted the significant role of gut microbiota in its pathogenesis. Alterations in the gut microbiome, known as dysbiosis, have been implicated in the onset and progression of autoimmune diseases, including SS. This review synthesizes current research on the impact of microbiota on SS, focusing on microbial dysbiosis, its impact on disease severity, and potential therapeutic interventions. Evidence indicates that specific microbial changes, such as reductions in beneficial bacteria and alterations in short-chain fatty acid (SCFA) production, correlate with increased disease activity and systemic inflammation. Microbiome-targeted therapies, including probiotics, prebiotics, and fecal microbiota transplantation, have shown promise in improving SS symptoms and modulating immune responses. Notably, butyrate and specific probiotic strains have demonstrated potential in reducing inflammation and enhancing salivary flow in preclinical studies. However, further research is needed to validate these findings and assess long-term efficacy. This review underscores the importance of gut microbiota in SS and suggests that microbiome-focused treatments could offer new avenues for managing this condition, improving patient outcomes, and potentially preventing disease onset.